Self-Introduction Training through Digital Marketing for Entrepreneurial Interest Development Among SMA Methodis Lubuk Pakam Students - Bambang Suwarno; Okta Jaya Hermanjaya; Feby Yoana Siregar (International Journal Of Community Service, 2025)
This training program titled "Self-Introduction through Digital Marketing for Entrepreneurial Interest Development Among SMA Methodis Lubuk Pakam Students" aims to equip high school students with essential digital marketing skills to foster entrepreneurial interest. In today’s digital era, understanding how to effectively use digital platforms for personal branding and marketing is crucial for young individuals aspiring to start their own businesses. This training covered foundational aspects of digital marketing, including social media management, content creation, and the utilization of digital platforms for entrepreneurship. Participants learned how to build a personal brand, create engaging content, and use e-commerce platforms and social media to promote business ideas. The training not only provided practical knowledge but also boosted the students’ confidence in pursuing entrepreneurship in a digitalized world. The outcomes of the training showed an increase in participants’ digital literacy, creativity, and entrepreneurial mindset, preparing them to explore future business opportunities effectively.